Operando high-pressure investigation of size-controlled CuZn catalysts for the methanol synthesis reaction - Núria J. Divins (Nature Portfolio, 2021)
The nature of the active species over Cu/ZnO catalysts for methanol synthesis remains elusive. Here, the authors shed light on the evolution of the nanoparticle/support interface and correlate its structural and chemical transformations with changes in the catalytic performance.